Análise da instrumentalidade do trabalho de assistentes sociais na saúde junto a idosos - Bastos, Karina Karla de Souza (2020)
This study aimed to analyze the instrumentality of the social worker in health care for the elderly. With regard to methodological aspects, it is a systematic bibliographic search, of the integrative type that followed the criteria and steps established by Lima and Mioto (2007). In addition to the bibliographic research, a documentary survey was also carried out to identify and read the available legislation, related to the category of Social Work. Regarding the “main sources”, the bibliographic research was based on the work of the National Meeting of Researchers in Social Work (ENPESS) of 2016 and 2018, and of the Brazilian Congress of Social Workers (CBAS) of 2013 and 2016, in addition to the articles from the A1 journals in the Social Service area: Revista Katálysis (UFSC) and Social Service & Society, taking as a “chronological parameter” the selection of works relating to the period from 2013 to 2018. The “linguistic parameter” was that of the Portuguese language. The research had as a universe the quantity of 4,917 articles and as a sample 14 articles specifically linked to the exercise of the social worker in the health area with the elderly. The historical-dialectical method was used and content analysis by categorization was used as the data analysis technique, using the synthesis matrix as an instrument using a reading script. The results of the research confirmed that the hypothesis was verified, since the instrumentality of the work of the social worker with the elderly in the health sector is mixed, with the strong presence of instrumental reason, dissociating from the perspective assumed by the Professional Ethical- Political Project, because the intentionality of the action sometimes comes up against objective working conditions. Thus, while the relationship between theory and practice is manifested only ideally, there is a superficial understanding of social phenomena, reducing professional practice to the technical dimension, in a fragmented and bureaucratic perspective. It is reiterated that the professional exercise must have as a horizon the articulation between the technical-operative, ethical-political and theoretical-methodological dimensions that, in their articulation, make it possible to effect the movement between the universal-singular-particular triad.